1999
DOI: 10.1002/(sici)1521-1878(199911)21:11<912::aid-bies3>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Signaling pathways are focused at specialized regions of the plasma membrane by scaffolding proteins of the MAGUK family

Abstract: The MAGUKs (membrane‐associated guanylate kinase homologs) are a family of proteins that act as molecular scaffolds for signaling pathway components at the plasma membrane of animal cells. They are localized in and required for the formation of several types of cell junctions, including epithelial tight and septate junctions as well as synaptic and neuromuscular junctions. They are also localized at the plasma membrane of other cell types, including erythrocytes, where they contribute to cell shape maintenance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
124
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(129 citation statements)
references
References 87 publications
2
124
0
1
Order By: Relevance
“…The IKK complex is also phosphorylated in a PKC-dependent manner and both modifications are essential for the IKK kinase activity. MAGUK domain that is believed to link proteins to the cytoplasmic membrane [62]. The second step for CAR-MA1 recruitment to the immunological synapse seems to be dependent on its inducible interaction with an adaptor protein known as ADAP (adhesion-and degranulationpromoting adapter protein).…”
Section: The Mechanism Of T Cell Receptor-induced Car-ma1 Activationmentioning
confidence: 99%
“…The IKK complex is also phosphorylated in a PKC-dependent manner and both modifications are essential for the IKK kinase activity. MAGUK domain that is believed to link proteins to the cytoplasmic membrane [62]. The second step for CAR-MA1 recruitment to the immunological synapse seems to be dependent on its inducible interaction with an adaptor protein known as ADAP (adhesion-and degranulationpromoting adapter protein).…”
Section: The Mechanism Of T Cell Receptor-induced Car-ma1 Activationmentioning
confidence: 99%
“…1A). PDZ domains are found in a variety of proteins, some of which localize at cell-cell junctions and function as scaffolding proteins (21,22), suggesting that vinexin may physiologically interact with this protein. Therefore, we focused on this clone in this study.…”
Section: Identification Of Lp-dlg/kiaa0583 As a Novel Vinexin Bindingmentioning
confidence: 99%
“…pyd ectopic bristles are due to the formation of additional SMCs (Chen et al, 1996;Takahisa et al, 1996) which appear to result from reduced transcription of emc in pyd mutant discs (Takahisa et al, 1996). Pyd is a PDZ domain protein whose sequence is closely related to mammalian Zona occludens proteins ZO-1, ZO-2 and ZO-3, members of the membrane-associated guanylate kinase homologue (MAGUK) family (reviewed in Dimitratos et al, 1999). Since Pyd is associated with septate and adherens junctions (Takahisa et al, 1996;Wie and Ellis, 2001), its role in emc regulation cannot be a direct one.…”
Section: Regulation Of Transcription and Translation Of Emcmentioning
confidence: 99%
“…Since Pyd is associated with septate and adherens junctions (Takahisa et al, 1996;Wie and Ellis, 2001), its role in emc regulation cannot be a direct one. The presence of multiple protein ± protein interaction domains in PDZ proteins allows them to act as sca olding components to organize protein complexes (Dimitratos et al, 1999). Accordingly, it has been suggested that Pyd participates in a signaling pathway that ultimately activates emc expression (Takahisa et al, 1996).…”
Section: Regulation Of Transcription and Translation Of Emcmentioning
confidence: 99%